POOR PERFORMANCE IN MATHEMATICS AMONG SENIOR SECONDARY SCHOOL STUDENTS: LESSONS FOR EDUCATION PLANNERS AND PARENTS - Bah, Yahya Muhammed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Education is one of the best tools to transform lives and living conditions especially with science and technology. Over the years, governments and families have been trying to ensure children access quality, relevant; and affordable education. In the areas of science and technology particularly at tertiary level, possessing strong mathematical knowledge and skills is a must. However, though the precise number is yet to be documented, children have been woefully failing the subject causing fears and panics in the general population more especially in the parents and government authorities as the future of development seemingly anchored on science and its applications. The fundamental rationale for the systematic review was to examine the causes of poor performance in mathematics among senior secondary school students. In summation, the study revealed that the causes of poor performance in mathematics among senior secondary school students are multifaceted and include causes located in personal status, erroneous beliefs, students, teachers, teaching methods, language competence, teaching and learning materials, parents and family members, schools, policies, society, infrastructures; and government To conclude, the poor performance in mathematics among senior secondary school students is negatively impacting their access to tertiary institutions for higher education in order to effectively take part in future national developments and worse of all, pushing them to commit crimes as they cannot secure jobs in the highly competitive job market.